12th IEEE International Symposium on Personal, Indoor and Mobile Radio Communications. PIMRC 2001. Proceedings (Cat. No.01TH859
DOI: 10.1109/pimrc.2001.965487
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulator for studying WCDMA based hierarchical cell structures

Abstract: A dynamic radio network simulator is implemented for studying WCDMA based Iiierarchical Cell Structures. The simulator allows estimation of capacity and quality of service related issues in a two-layer network. The input to the simulator is base station and mobile station information and its output is presented as the blocking and dropping probabilities, handoff rate and capacity of the assumed network. In this paper both uplink and downlink are considered. As an example, the impact of between-layer handover o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A full motion or dynamic system level simulator for the downlink, based on the UMTS air interface specifications [24], has been developed to verify the results of this study [25]. The simulator with a time-driven simulation engine in it, recalculates mobile positions, path-losses, mobile station cell ownerships and generates call originating/clearing events and determine the E b /I o , at regular time intervals.…”
Section: System Level Simulatormentioning
confidence: 99%
“…A full motion or dynamic system level simulator for the downlink, based on the UMTS air interface specifications [24], has been developed to verify the results of this study [25]. The simulator with a time-driven simulation engine in it, recalculates mobile positions, path-losses, mobile station cell ownerships and generates call originating/clearing events and determine the E b /I o , at regular time intervals.…”
Section: System Level Simulatormentioning
confidence: 99%
“…Accurate system level simulations are required for the assessment of the network performance under different conditions. Some previous studies related to load control and system level simulators can be found in [1], [2], [3], [4], [5], [7].…”
Section: Introductionmentioning
confidence: 99%
“…A dynamic system level simulator [6] for the downlink that is based on the UMTS air interface specifications [7] has been developed. Seven cells, including the given cell in the center and six adjacent cells in the first tier are simulated, with a wrap around effect to keep the density of the users fixed.…”
Section: Simulation and Resultsmentioning
confidence: 99%